ANALISIS PERUBAHAN KUANTITAS MATERIAL KOLOM BETON BERTULANG PADA MODEL STRUKTUR BANGUNAN GEDUNG SEDERHANA - Mubarak Mubarak; Abdullah Abdullah; Medyan Riza; Yulia Hayati (Rekayasa Sipil, 2019)
The loading aspect of a building is one of the factors that varies the dimensions of building components. Differences in building site areas are also contributed to the load received by buildings, especially in terms of earthquake loads. For the Province of Aceh with relatively high levels of earthquake vulnerability, the problems of structure dimensions change that caused by earthquake need to be specified. Changes to dimensions will affect the quantity of works, and furthermore against the building price standard. This research conducted to analyze the change of material quantity caused by earthquake load changes based on indication of acceleration of spectral response. This study was conducted by developing a model of simple building structure design and load change analyzed in 8 earthquake zones. The analysis focused specifically on the structural components of reinforced concrete columns. The information obtained from the analysis explains the effect of earthquake load changes from each of the observed zones on the use of reinforcing steel materials. The same condition is also seen in the ratio of reinforcement usage per cubic meter of concrete. The changes begin to be seen when the building model is positioned on zone 14 with an acceleration of 1.19g spectrum response.